PS 11-24 IMPACT OF BLOOD PRESSURE LEVEL ON ACETYLCOHOLINE INDUCED CORONARY ARTERY SPASM. (September 2016) - Lee, Eun Mi; Seo, Hong Seog; Choi, Man Ho; Kim, Hyun Ki; Yun, Kyeong Ho; Choi, Byoung Geol; Na, Jin Oh; Choi, Cheol Ung; Kim, Jin Won; Rha, Seung-Woon; Park, Chang Gyu; Oh, Dong Joo
Abstract : Objective: Although autonomic nervous system activity may play an important role in coronary artery spasm (CAS), few studies have been published on the relationships between CAS and blood pressure (BP) level. This study was aimed to investigate the relationship between CAS and BP levels. Design and Method: A total of 5, 304 consecutive patients with resting chest pain and without significant stenosis who underwent ACH provocation testing were enrolled.1193 patients were excluded owing to miscellaneous reasons and finally, 4, 102 patients were included. Patients were categorized by BP levels. Significant CAS was defined as ≥ 70% narrowing by ACH provocation. To adjust potential confounders, a propensity score matched (PSM) analysis was performed using the logistic regression model. Results: After PSM analysis, frequency of CAS was analyzed according to BP level. (5 models; <115 mmHg vs 115–124 (model 1), 125–134 (model 2), 135–144 (model 3), 145–155 (model 4), ≥155 mmHg (model 5), respectively). In overall patients, frequency of CAS was significantly lower in model 4 and 5 [model 4–379 pairs, C-statistic = 0.723, CAS case 186 (49%), PSM RR 0.74 (CI 0.55–0.98), p = 0.042; model 5–385 pairs, C-statistic = 0.746, CAS case 200 (51.9%), PSM RR 0.70 (CI 0.52–0.93), p = 0.017]. In normotensives, frequency of CAS was significantly lower in in model 5 (150 pairs, C-statistic = 0.772, CAS case 82 (54.6%), PSM RR 0.60 (CI 0.37–0.96), p = 0.034). Whereas, in hypertensives, CAS was not associated with BP level. Multivariate analysis showed that CAS was positively associated with age, male gender, body mass index, myocardial bridge, baseline spasm (narrowing ≥30%) but negatively associated with BP level. Conclusions: These results suggest that Ach-induced CAS is inversely associated with BP level.